Petroleum hydrocarbon release behavior study in oil-sediment aggregates: turbulence intensity and chemical dispersion effect. Issue 14 (11th March 2019) - Yan, Dong; Meng, Long; Li, Haoshuai; Song, Tianwen; Sun, Peiyan; Bao, Mutai; Li, Ximing
Abstract : This study investigated the effects of turbulence and oil dispersants on release of petroleum hydrocarbons in oil-sediment aggregates. Abstract : This study investigated the effects of turbulence and oil dispersants on release of petroleum hydrocarbons in oil-sediment aggregates. A kinetic study showed that the static oil release process could be fitted to the first-order kinetics model. The oil concentration increased with increasing temperature and salinity, while remaining independent of pH. The dispersant desorption ability of petroleum hydrocarbons followed the sequence of: Tween 80 > Tween 85 > Span 80 > DOSS. In the presence of turbulence, the maximum release ratio was 40.28%. However, the combination of dispersants and turbulence had a smaller effect than turbulence alone. Furthermore, residual n -alkanes and PAHs in the sediments were analyzed. The results showed higher proportions of C15 –C35 and 2–3 ring PAHs in residual oil. These results can help assess the fate and distribution of oil spills in marine environments.